(untitled) (Advances in Civil and Architectural Engineering, 2021)
In this study, a comparison of the strength and durability of concrete with sulfate-resistant cement and cement with pozzolana additive was performed. In assessing the concrete durability, three indicators were compared: sulfate resistance, water permeability, and frost resistance. All concrete mixtures were used without admixtures. The absence of chemical admixtures in the concrete mixtures was because of the need to compare properly the properties of concretes with different cements without the influence of modifiers, which may result in different efficiencies for different types of binders. The concrete compositions of grades C20/25 and C30/35 were presented. The use of Portland cement with pozzolana additive in concrete mixtures provided the necessary level of corrosion resistance and frost resistance of concrete, as well as higher water permeability and lower cement content in comparison with using sulfate-resistant Portland cement.